Decision model for determining the ownership structure of chemical park units, Integration of decision-making techniques and data envelopment analysis - Darush Mohamadi Zanjirani (Journal of Asset Management and Financing)
The importance of global markets and the growth of competition has led to a new division of work in the global and national economy. Such changes have caused attention to specific business issues such as obtaining resources, sharing information, and forming supply chain relationships for small companies and even large companies that try to form industrial parks. One of these changes is merger and acquisition, which is considered as a theoretical basis in the park formation. The present research has been carried out with the aim of providing a model to identify and apply factors that promote acquisition among the production units of a chemical park. The research method is descriptive-analytical, which uses various techniques of decision theory to determine the pattern of acquisition and ownership share of production units, financing and investment strategies, and the levels of integration and acquisition of the downstream units of the park . The application of the multi-criteria methodology and the design of the decision support system has made the park developer company's decision-making easier in the selection of production units, with the quantitative goals of the amount of ownership, acquisition and investment.